Letter: a potassium‐competitive acid blocker vs a proton pump inhibitor for healing endoscopic submucosal dissection‐induced artificial ulcers after treatment of gastric neoplasms. Issue 5 (4th August 2017) - Ban, H.; Sugimoto, M.; Otsuka, T.; Murata, M.; Nakata, T.; Hasegawa, H.; Fukuda, M.; Inatomi, O.; Bamba, S.; Kushima, R.; Andoh, A.
Abstract : Linked Content This article is linked to Kagawa et al and Iwamuro and Inaba papers. To view these articles visithttps://doi.org/10.1111/apt.14213 andhttps://doi.org/10.1111/apt.13747 .